2019
DOI: 10.1021/acsomega.9b00914
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Catalytic Degradation of Brilliant Green by Spinel Zinc Ferrite Sheets

Abstract: Microwave (MW)-assisted catalytic degradation, being an emerging technique, can potentially fill in the technological gap which promises on-demand , prompt, and efficient catalysis, and therefore, suitable MW catalysts are curiously being hunted. Candidature of spinel zinc ferrite (SZFO) atomic sheets as a MW catalyst has thoroughly been investigated in this article. Analytical techniques prove SZFO atomic sheets to be highly crystalline, thermally stable, good dielectric, and superparam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 49 publications
(91 reference statements)
1
17
0
Order By: Relevance
“…A comparison between the photodegradation of brilliant green, rhodamine B, and the binary-dye solution after the addition of scavengers (Figure 7) indicates that brilliant green dye degradation efficiency by ZnS-1 decreases from 71.62% (no scavenger) to 36.30% (SN), 61.99% (AC), and 67.65% (IPA) while its degradation by ZnS-2 decreases from 91.06 to 32.72%, 79.26%, and 81.46%, and with ZnS-3 it decreases from 94.61% to 50.28%, 84.37%, and 88.59%, respectively. This shows that the dominant active species are e − and •O 2 − , while •OH − acts as a secondary active species, which agrees with the trend observed with other catalysts [57,58]. However, the degradation efficiency of rhodamine B (RhB) by ZnS-1 decreases from 45.12% (no scavenger) to 29.89% (IPA), 14.33% (SN) and 19.79% (AC) whereas with ZnS-2 the degradation efficiency decreases from 56.69 (no scavenger) to 29.06% (IPA), 16.31% (SN) and 23.45 (AC).…”
Section: Effect Of Irradiation Time On Photocatalytic Degradationsupporting
confidence: 91%
“…A comparison between the photodegradation of brilliant green, rhodamine B, and the binary-dye solution after the addition of scavengers (Figure 7) indicates that brilliant green dye degradation efficiency by ZnS-1 decreases from 71.62% (no scavenger) to 36.30% (SN), 61.99% (AC), and 67.65% (IPA) while its degradation by ZnS-2 decreases from 91.06 to 32.72%, 79.26%, and 81.46%, and with ZnS-3 it decreases from 94.61% to 50.28%, 84.37%, and 88.59%, respectively. This shows that the dominant active species are e − and •O 2 − , while •OH − acts as a secondary active species, which agrees with the trend observed with other catalysts [57,58]. However, the degradation efficiency of rhodamine B (RhB) by ZnS-1 decreases from 45.12% (no scavenger) to 29.89% (IPA), 14.33% (SN) and 19.79% (AC) whereas with ZnS-2 the degradation efficiency decreases from 56.69 (no scavenger) to 29.06% (IPA), 16.31% (SN) and 23.45 (AC).…”
Section: Effect Of Irradiation Time On Photocatalytic Degradationsupporting
confidence: 91%
“…Mishra et al studied the Microwave-Assisted Catalytic Degradation of brilliant green (an organic pollutant, a derivative of triarylmethane dye, present in water due to industrial waste), using spinel zinc ferrite sheets (SZFO) [213]. The reported results demonstrated that brilliant green was chemisorbed on the SZFO atomic sheets, mineralized when exposed to MW irradiation in 5 min, and the overall efficiency has been observed to be >99%.…”
Section: Microwaves As Alternative Of the Conventional Advanced Oxidamentioning
confidence: 99%
“…Mishra et al used the co-precipitation method to synthesize spinel zinc ferrite (SZFO) atomic sheets. With the aid of microwave irradiation, it showed excellent degradation performance for bright green, and the degradation efficiency was greater than 99% within 5 min (Mishra et al, 2019 (Sun and Li, 2020). Mesoporous zinc ferrite, agglomeration of nanoparticles with size of 5-10 nm, was prepared by Su et al In the presence of visible light and hydrogen peroxide, the degradation efficiency of AOII reaches almost 100% within 2 h (Su et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Sepiolite is composed of two silicon-oxygen tetrahedrons sandwiching a magnesium-oxygen octahedron and the discontinuity of the silicon-oxygen tetrahedron makes the sepiolite have a rich internal tunnel structure. Benefit from the unique structure and composition, sepiolite fibers possess large specific surface area, high porosity and various functional groups, which provides more reaction sites for supported catalysts (Ma and Zhang, 2016;Wang et al, 2017;Zhang et al, 2017;Mishra et al, 2019;Cui et al, 2020). In addition to its abundant storage, low cost and environmental friendliness, sepiolite is an ideal candidate for catalyst carrier (Xu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%